High acceptance of home-based HIV counseling and testing in an urban community setting in Uganda - Mugerwa Micheal; List Justin; Sempeera Hassard; Sekandi Juliet N; Asiimwe Stephen; Yin Xiaoping; Whalen Christopher C (BMC, 2011)
Abstract Background HIV testing is a key component of prevention and an entry point into HIV/AIDS treatment and care however, coverage and access to testing remains low in Uganda. Home-Based HIV Counseling and Testing (HBHCT) has potential to increase access and early identification of unknown HIV/AIDS disease. This study investigated the level of acceptance of Home-Based HIV Counseling and Testing (HBHCT), the HIV sero-prevalence and the factors associated with acceptance of HBHCT in an urban setting. Methods A cross-sectional house-to-house survey was conducted in Rubaga division of Kampala from January-June 2009. Residents aged ≥ 15 years were interviewed and tested for HIV by trained nurse-counselors using the national standard guidelines. Acceptance of HBHCT was defined as consenting, taking the HIV test and receipt of results offered during the home visit. Multivariable logistic regression analysis was performed to determine significant factors associated with acceptance of HBHCT. Results We enrolled 588 participants, 408 (69%, 95% CI: 66%-73%) accepted testing. After adjusting for confounding, being male (adj. OR 1.65; 95%CI 1.03, 2.73), age 25-34 (adj. OR 0.63; 95% CI 0.40, 0.94) and ≥35 years (adj. OR 0.30; 95%CI 0.17, 0.56), being previously married (adj. OR 3.22; 95%CI 1.49, 6.98) and previous HIV testing (adj. OR 0.50; 95%CI 0.30, 0.74) were significantly associated with HBHCT acceptance. Of 408 who took the test, 30 (7.4%, 95% CI: 4.8%- 9.9%) previously unknown HIV positive individuals were identified and linked to HIV care. Conclusions Acceptance of home-based counseling and testing was relatively high in this urban setting. This strategy provided access to HIV testing for previously untested and unknown HIV-infected individuals in the community. Age, sex, marital status and previous HIV test history are important factors that may be considered when designing programs for home-based HIV testing in urban settings in Uganda.